The effects of joint economic enterprises (JEE) on the levels of income and agricultural production of agrarian reform beneficiaries (ARBs) in Barangay Tamayong Davao City - Genise, Jodylene O.
The study attempted to analyze whether Joint Economic Enterprises (JEE) had brought significant effects on the level of income and agricultural production of Agrarian Reform Beneficiaries (ARBs) in Barangay Tamayong, Davao City. JEE is defined as the partnership of beneficiaries and investors, were taken in the forms of Lease Contract (LC) and Production, Management and Processing Agreement (PMPA). The level of income was measured in terms of sum of money derived from economic activities such as on-farm, off-farm and non-farm economic activities. Level of production was measured in terms of its value, calculated as the level of output, at a given price. Mean values of the levels of income and production before JEE were compared with those after JEE. Results show that in terms of income, JEE had significant effects to on-farm and off-farm income levels. On the levels of productions JEE was found to have significantly increased the output level of ARBs engaged in PMPA scheme.